2023
DOI: 10.1093/brain/awad058
|View full text |Cite
|
Sign up to set email alerts
|

GGC repeat expansion in NOTCH2NLC induces dysfunction in ribosome biogenesis and translation

Abstract: GGC repeat expansion in the 5′ untranslated region (UTR) of NOTCH2NLC is associated with a broad spectrum of neurological disorders, especially neuronal intranuclear inclusion disease (NIID). Studies have found that GGC repeat expansion in NOTCH2NLC induces the formation of polyglycine (polyG)-containing protein, which is involved in the formation of neuronal intranuclear inclusions. However, the mechanism of neurotoxicity induced by NOTCH2NLC GGC repeats is unclear. Here, we used NIID patient-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated the neurotoxicity of uN2CpolyG protein based on its reduction of cell viability, disruption of nucleocytoplasmic transport, induction of mitochondrial dysfunction, and inhibition of ribosome biogenesis and translation (3,(17)(18)(19). These ndings have offered crucial insights into the protein's detrimental effects on cellular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the neurotoxicity of uN2CpolyG protein based on its reduction of cell viability, disruption of nucleocytoplasmic transport, induction of mitochondrial dysfunction, and inhibition of ribosome biogenesis and translation (3,(17)(18)(19). These ndings have offered crucial insights into the protein's detrimental effects on cellular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have proposed several hypotheses regarding the pathogenesis of NIID, including the toxicity of polyamino acid proteins (17)(18)(19), toxic RNA gain-offunction (19,20), and aberrant methylation of GGC repeat sequences (21). Recently, some studies have suggested that dysfunction of ribosome biogenesis and translation and mitochondrial dysfunction might be related to the pathogenesis of NIID (22,23). However, the speci c mechanisms driving the pathogenesis of NIID remain unclear, and extensive experiments in cellular and animal models are required for further studies.…”
Section: Pathogenesis Of Niidmentioning
confidence: 99%